Solid Pseudopapillary Tumor of the Pancreas (Frantz’s Tumor): Case Report - Monção, Carlos Rafael Lima (2020)
Introduction: The solid pseudopapillary tumor of the pancreas (Frantz’s tumor) is a neoplasm extremely rare that represents less than 1% of all the pancreatic tumors. Case report: 48 years old female patient was hospitalized with intra-abdominal mass of etiology hard to define. She was submitted to surgical treatment with successful laparotomy tumor resection and there were no postoperative complications. The patients usually become symptomatic only after long time of evolution, when they have discomfort or abdominal pain or palpation of abdominal masses during physical examination. Complementary exams like ultrasound and computed tomography are necessary to diagnosis and usually they show heterogeneous large intra-abdominal masses. It is necessary the confirmation with anatomopathological study which usually has histological characteristics compatible with low-grade malignancy. The surgical resection is the recommended treatment and even large size tumors has a considerable chance of cure if free surgical margins are obtained. It is known that complete tumoral resection is associated with long-term survival. Conclusion: The solid pseudopapillary tumor of the pancreas (Frantz’s tumor), although rare, should be considered in differential diagnosis of pancreatic neoplasms because surgical treatment usually has good chances of cure even in large size tumors.